A human factors and ergonomics approach to conceptualizing care work among caregivers of people with dementia. (October 2022) - Werner, Nicole E.; Rutkowski, Rachel A.; Holden, Richard J.; Ponnala, Siddarth; Gilmore-Bykovskyi, Andrea
Abstract: Society relies upon informal (family, friend) caregivers to provide much of the care to the estimated 43.8 million individuals living with Alzheimer's disease and related dementias globally. Caregivers rarely receive sufficient training, resources, or support to meet the demands associated with dementia care, which is often associated with increased risk of suboptimal outcomes. Human factors and ergonomics (HFE) can address the call for new approaches to better understand caregiving and support caregiver performance through systematic attention to and design of systems that support the work of caregivers– their care work. Thus, our objective was to perform a work system analysis of care work. We conducted a qualitative study using a Critical Incident Technique interviewing approach and Grounded Dimensional Analysis analytic procedures. Our findings introduce a new conceptual framework for understanding the care work system of dementia caregivers and suggest that care work is influenced by interactions among distinct caregiver goals, the task demands of the care needs of the person with dementia, daily life needs of the caregiver and family, and contextual factors that shape caregivers' perceptions surrounding care. The initial work system model produced by this study provides a foundation from which future work can further elucidate the care work system, determine how the care work system intersects and coordinates with other work systems such as the patient work system, and design systems that address caregivers' individual caregiving context. Highlights: Dementia caregivers are often under supported to meet caregiving demands. Systematic design of care work systems that support care work is needed. Findings introduce a goal- and feedback-driven dementia care work system. Interactions among caregiver goals, demands, and perceptions influence care work. Caregiver journey concept—care work is longitudinal, boundary-spanning, dynamic.